Association Between Perioperative Glycemic Control Strategy and Mortality in Patients With Diabetes Undergoing Cardiac Surgery: A Systematic Review and Meta-Analysis - Jin, Xinye; Wang, Jinjing; Ma, Yanfang; Li, Xueqiong; An, Ping; Wang, Jie; Mao, Wenfeng; Mu, Yiming; Chen, Yaolong; Chen, Kang (Frontiers in Endocrinology, 2020)
Objective: To analyze association between different perioperative glycemic control strategies and postoperative outcomes in patients with diabetes undergoing cardiac surgery. Methods: PubMed, Cochrane Library, Web of Science, EMBASE, Wanfang Data, China National Knowledge Infrastructure (CNKI) and CBM were searched from inception to January 31th, 2019. Two researchers independently screened the literature, extracted data, and evaluated the risk of bias of included studies, and consensus was reached by discussion with a third researcher. Results: 6 RCTs were included in the meta-analysis. We analyzed the effect of liberal (>180mg/dL or 10.0mmol/L), moderate (140-180mg/dL or 7.8-10.0mmol/L) and strict (<140mg/dL or 7.8mmol/L) glycemic control strategies in patients with diabetes undergoing cardiac surgery. The pooled results showed that a strict glycemic control strategy was associated with a significantly lower risk of atrial fibrillation (OR=0.48, 95%CI [0.32, 0.72], P<0.001) and sternal wound infection (OR=0.28, 95%CI [0.14, 0.54], P<0.001), while there was no significant differences in postoperative mortality, stroke and hypoglycemic episodes when compared with moderate control. In addition, there is no significant difference between moderate versus liberal glycemic control strategies in postoperative mortality. However, moderate control was beneficial for reduction in atrial fibrillation (OR=0.28, 95%CI [0.13, 0.60], P=0.001) versus liberal glycemic control strategy. Conclusions: This meta-analysis showed when compared with moderate glycemic control strategy in patients with diabetes undergoing cardiac surgery, maintained strict glycemic control is associated with low risk of atrial fibrillation and sternal wound infection. No additional benefits were found in liberal glycemic control strategy.